IMPLEMENTATION OF LAW ENFORCEMENT OF HAND-CATCHING OPERATIONS (OTT) IN LAW NUMBER 19 OF 2019 - Aprilia Krisdayanti; Edelweiss Premaulidiani Putri (KLAUSULA (Jurnal Hukum Tata Negara Adminitrasi Dan Pidana), 2023)
Corruption in Indonesia is increasingly becoming a topic of discussion along with the debate over the revision of the KPK Law and the election of a new chairman of the "anti-racial" institution to cause a wave of protests among the public, the revision of the KPK Law is considered not to take into account public aspirations and the points of change are feared to weaken the performance of the institution in eradicating corruption. There are two techniques that have legal flaws in conducting hand-catching operations. Wiretapping is only regulated in general only in Law No. 30 of 2002, while entrapment is not known in various regulations on corruption in Indonesia which were previously contained in Article 31 paragraph (1) of Law No. 11 of 2008 concerning Electronic Information and Transactions but have been abolished. In order to eradicate corruption, the law authorizes the KPK to intercept, therefore, if these two techniques are used, it often gives rise to the assumption that the KPK has violated the law and human rights, namely violating the confidentiality / private of a person. This study aims to find out the extent of Law No. 19 of 2019 concerning the KPK in minimizing corruption cases in Indonesia, as well as obstacles after the implementation of the latest KPK Law This research uses empirical juridical research methods, or also known as field research, namely research that examines applicable legal provisions and the reality of what happens in society with empirical and sociological juridical approaches. The data used are primary, secondary, and tertiary data. primary legal materials consist of the Criminal Code (Criminal Code), KUHAP (Criminal Procedure Code), Law Number 20 of 2001 concerning Corruption Crimes, Law Number 30 of 2002 concerning the Corruption Eradication Commission, Law No. 19 of 2019 second amendment to Law No. 30 of 2002 concerning the Corruption Eradication Commission (KPK), secondary legal materials in the form of scientific journals, book and other related documents, tertiary legal materials in the form of legal dictionaries. After Law 19/2019, there was the authority of the KPK which was finally transferred regarding wiretapping, seizure, and searches before did not need permission, immediately given a warrant the direct leadership could arrest. Meanwhile, after the enactment of Law 19/2019, there must be permission from the supervisory board Regarding Law 19/2019 after the Constitutional Court's decision because there was a material test, then the Constitutional Court decision number 70 of 2019 regarding material testing emerged, the Supervisory Board was given the authority to supervise the Leaders and Employees of the Corruption Eradication Commission, and it was not appropriately positioned and functioned as 57 licensing organs (vergunningsorgaan). From an Administrative Law perspective, the Board of Trustees cannot act as a vergunningsorgaan. based on Article 37B paragraph 1 letter b of Law No. 19 of 2019 which reads; "Granting permission or not granting permission for wiretapping, search, and/or seizure" contains discretionary meanings held by the Board of Trustees.